Preparation and Properties of Perovskite Solar Cells by PEAI Surface Treatment - Zhao, Yunpeng; Bala, Hari; Cheng, Fei; Wen, Yingjie; Wang, Boji (International Journal of Materials Science and Technology Studies, 2025)
In this study, a higher quality MA0.9FA0.1PbI2.85Br0.15 film was surface treated with phenylethylamine iodide (PEAI), and a perovskite solar cell (PSC) with high stability and high efficiency carbon pair electrode was prepared. The I- and PEA+ ions in PEAI fill the defects between the perovskite crystals, passivate the surface, improve the quality of the film, increase the size of the perovskite grains, reduce the carrier recombination, and enhance the optical properties. By comparing and testing the effect of a series of different PEAI solution concentrations on the quality of MA0.9FA0.1PbI2.85Br0.15 film, the optimal concentration of PEAI solution is 1.5mg /mL, and the optimal PCE of the device is 11.25%. PSCs were higher than those of untreated MA0.9FA0.1PbI2.85Br0.15 films. The unpackaged and PEAI solution surface treated battery devices are more stable in an air atmosphere, and the PCE of the device after 60 days remains at 96% of the initial PCE.